The Role of Mangrove Ecotourism in Community Empowerment and Sustainability Environment: Study Case Tanjung Batu Village Central Sekotong, West Lombok - Dian Aryani; Ibrahim Ibrahim (Journal of Governance and Spatial Planning, 2026)
Mangrove ecotourism is one of the strategic approaches in management source Power coast that offers benefit economic, social, and ecological research This aim analyzes influence mangrove ecotourism and empowerment public to sustainability environment in the village Tanjung Batu, Central Sekotong, West Lombok. Method study uses quantitative correlational with 30 selected respondents​ through simple random sampling and equipped with qualitative data in the form of observation, interviews, and FGD. Data analysis includes descriptive statistics, multiple linear regression, ANOVA, and coefficient regression. Research results show that empowerment public influential significant to sustainability environment (β = 0.808; p < 0.001), whereas mangrove ecotourism is not influential significant (p = 0.605). Although thus, the regression model in a way overall own strength predictive tall with R² = 0.782. Findings This confirm that sustainability environment is more determined by involvement active public compared to variables facilities and activities tour solely. Research This give implications important for planning ecotourism-based communities in coastal areas.